PERILAKU KONSUMTIF PETANI PADI DI NAGARI SUPAYANG: PERSPEKTIF JEAN BAUDRILLARD - Satri Nuryulhaida (Prodi Sosiologi FISIP UPR, 2024)
This research is motivated by the emergence of consumptive behavior among rice farmers in Nagari Supayang. Despite residing in a rural area, these farmers exhibit consumption patterns that are disproportionate to their actual income levels. The main objective of this study is to identify the forms of consumptive behavior among rice farmers in Nagari Supayang and to analyze the factors that drive such behavior. This study employs a qualitative research design with a descriptive approach. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The validity of the data was ensured through prolonged observation, increased rigor, and triangulation of sources, techniques, and time. The results reveal several forms of consumptive behavior among rice farmers in Nagari Supayang, Payung Sekaki District, Solok Regency. These include the purchase of goods beyond primary needs, excessive use of fertilizers and pesticides, substantial expenditures for wedding ceremonies, and the acquisition of luxury items. The factors contributing to this consumptive behavior include temporary increases in income, social environmental influences, easy access to credit or loans, the impact of media and advertising, as well as environmental or natural factors